Experimental Basis for Creating an Osseointegrated Neural Interface for Prosthetic Control: A Pilot Study in Rabbits. (19th February 2020) - Dingle, Aaron M; Ness, Jared P; Novello, Joseph; Millevolte, Augusto X T; Zeng, Weifeng; Sanchez, Ruston; Nemke, Brett; Lu, Yan; Suminski, Aaron J; Markel, Mark D; Williams, Justin C; Poore, Samuel O
ABSTRACT: Introduction: While debate persists over how to best prevent or treat amputation neuromas, the more pressing question of how to best marry residual nerves to state-of-the-art robotic prostheses for naturalistic control of a replacement limb has come to the fore. One potential solution involves the transposition of terminal nerve ends into the medullary canal of long bones, creating the neural interface within the bone. Nerve transposition into bone is a long-practiced, clinically relevant treatment for painful neuromas. Despite neuropathic pain relief, the physiological capacity of transposed nerves to conduct motor and sensory signals required for prosthesis control remains unknown. This pilot study addresses the hypotheses that (1) bone provides stability to transposed nerves and (2) nerves transposed into bone remain physiologically active, as they relate to the creation of an osseointegrated neural interface. Methods: New Zealand white rabbits received transfemoral amputation, with the sciatic nerve transposed into the femur. Results: Morphological examination demonstrates that nerves remain stable within the medullary canal, while compound nerve action potentials evoked by electrical stimulation of the residual nerve within the bone could be achieved at 12 weeks ( p < 0.0005). Conclusion: Transposed nerves retain a degree of physiological function suitable for creating an osseointegrated neural interface.